Understanding the behaviour of (macro)chain transfer agents for RAFT controlled dispersion polymerisation in supercritical CO2 - Alves Costa Pacheco, Ana Patricia (2022)
In this thesis, we focus on reversible addition- fragmentation chain transfer (RAFT) polymerisation in scCO2 with both molecular chain transfer agents (CTAs) (DDMAT, CPAB, CTPPA) and polydimethylsiloxane (PDMS)-based macromolecular CTAs (macro-CTAs) soluble in scCO2 (PDMS-DDMAT, PDMS-CPAB, PDMS-CTTPA), for the dispersion polymerisation of methyl methacrylate (MMA). Although the use of PDMS-DDMAT macro-CTAs led to stable PMMA particles, successful RAFT control was not attained, and part of the macro-CTA remained unreacted. Therefore, RAFT dispersion polymerisation of MMA in scCO2 was investigated using DDMAT and comparing to other molecular CTAs. Despite its low chain transfer constant (Ctr) towards MMA, DDMAT showed good control over PMMA molecular weight. A thorough investigation of the nucleation stage revealed an unexpected “in situ two-stage” mechanism that explains this result. Finally, a correlation between polymerisation control and the degree of solubility in scCO2 of the CTAs was stablished, giving rise to a guideline to select the best molecular CTA for MMA RAFT dispersion polymerisation in scCO2. The use of PDMS-CPAB and PDMS-CTPPA, which present chain-ends of high Ctr towards MMA, allowed an overall improvement of MMA polymerisation and RAFT control in scCO2 compared with PDMS-DDMAT. The good solubility of these macro-CTAs in scCO2 and the good control observed led to the formation of PDMS-b-PMMA block copolymers, suggesting the establishment of a polymerisation-induced self-assembly (PISA) process. This is a step forward towards PISA polymerisation via RAFT in scCO2 with fluorine-free macro-CTAs.